Mesoporous Titania‐Iron(III) Oxide with Nanoscale Porosity and High Catalytic Activity for the Synthesis of β‐Amino Alcohols and Benzimidazole Derivatives. Issue 17 (5th August 2015) - Roy, Susmita; Banerjee, Biplab; Salam, Noor; Bhaumik, Asim; Islam, Sk. Manirul
Abstract A mesoporous TiO2‐Fe2O3 mixed oxide material (MTF‐1E) with nanoscale porosity and a high BET surface area was synthesized using sodium dodecyl sulfate (SDS) as a structure‐directing agent. The material was characterized by powder XRD, high‐resolution TEM, N2 sorption, and NH3 temperature‐programmed desorption studies. The catalyst shows an excellent regioselectivity for the ring‐opening of epoxides with amines under solvent‐free conditions at room temperature for the synthesis of a series of β‐amino alcohols. It also showed a very high catalytic efficiency for the synthesis of benzimidazole derivatives in water. The catalyst can be recovered easily from the reaction medium and reused six times without a significant decrease in its catalytic activity and selectivity.